80.8k views
2 votes
If g(x)=x³ + 2x² - 6 find g(0), g(-2), g(-1), g(-2) -1 , g(0) + 2

User Sijith
by
4.2k points

1 Answer

3 votes

ANSWER:


\begin{gathered} g(0)=-6 \\ g(-2)=-6 \\ g(-1)=-5 \\ g(-2)-1=-5 \\ g(0)+2=-8 \end{gathered}

Explanation:

We have the following function:


g\mleft(x\mright)=x^3+2x^2-6

We calculate in each case:


\begin{gathered} g(0)=0^3+2\cdot0^2-6=-6 \\ g(-2)=(-2)^3+2\cdot(-2)^2-6=-8+8-6=-6 \\ g(-1)=(-1)^3+2\cdot(-1)^2-6=-1+2-6=-5 \\ g(-2)-1=-6\rightarrow g(-2)=-6+1=-5 \\ g(0)+2=-6\rightarrow g(0)=-6-2=-8 \end{gathered}

User Dustin Sun
by
4.2k points